2001
DOI: 10.1038/sj.cdd.4400843
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a lysosomal pathway for apoptosis induced by the synthetic retinoid CD437 in human leukemia HL-60 cells

Abstract: The novel synthetic retinoid 6-[3-(1-adamantyl)-4-hydroxyphenyl]-2-naphtalene carboxylic acid (AHPN/CD437) has been proven to be a potent inducer of apoptosis in a variety of tumor cell types. However, the mechanism of its action remains to be elucidated. Recent studies suggest that the lysosomal protease cathepsin D, when released from lysosomes to the cytosol, can initiate apoptosis. In this study, we examined whether cathepsin D and free radicals are involved in the CD437-induced apoptosis. Exposure of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 34 publications
1
90
1
Order By: Relevance
“…Generation of reactive oxygen species has been reported for CD437. 4,24 However, in our cell system, we did not detect modifications of mitochondrial trans-membrane potential nor ROS generation by ST1926 after 3-6 h exposure (data not shown). In keeping with this finding was the inability of antioxidant agents (e.g.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Generation of reactive oxygen species has been reported for CD437. 4,24 However, in our cell system, we did not detect modifications of mitochondrial trans-membrane potential nor ROS generation by ST1926 after 3-6 h exposure (data not shown). In keeping with this finding was the inability of antioxidant agents (e.g.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, atypical retinoids exert growth-inhibitory activity and induce apoptosis in retinoid-resistant cells, and these cellular effects cannot be blocked by RARantagonists. [2][3][4] Multiple mechanisms, including activation of JNK and p38, have been implicated in apoptosis induced by atypical retinoids. 5 However, the mechanism of the growthinhibitory activity and the cellular basis of the broad spectrum of activity of these compounds remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…5,8,9 Why should inhibition of just one cathepsin be detrimental for NB cell survival? It has been previously shown that deficiency of CD or inhibition of either CD or CB does not compromise overall turnover of long-lived proteins.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Recently, proteases resident within the endosomal-lysosomal compartment (cathepsins) have also been associated with apoptosis. [5][6][7][8][9] These studies demonstrated the need for a cathepsin-mediated proteolytic event in the apoptotic pathway triggered by cytokines or antiblastic drugs. In addition, the active participation of the autophagic proteolytic pathway, particularly of lysosomal cathepsins B and D (CB, CD), has been envisaged in rat pheochromocytoma PC12 cell death after nutrient and serum factor deprivation.…”
mentioning
confidence: 94%
“…In contrast, p53-induced cell death involved early lysosomal damage, followed by mitochondria damage, which was blocked by BHA (25). Cathepsin D release preceded ROI production in the course of retinoid-induced HL60 cell death (28). In TWEAK-stimulated hFn14/L5178Y cells, cathepsin B release was abrogated by antioxidant BHA (Fig.…”
Section: Characterization Of Tweak-induced Cell Death In Hfn14 Transfmentioning
confidence: 93%